Case Report: Overlapping Syndrome of Anti-NMDAR Encephalitis and MOG Inflammatory Demyelinating Disease in a Patient With Human Herpesviruses 7 Infection - Li, Sisi; Wang, Minjin; Li, Hancong; Wang, Jierui; Zhang, Qi; Zhou, Dong; Li, Jinmei (Frontiers in Immunology, 2022)
Objectives: This study reported a case of overlapping anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis and myelin oligodendrocyte glycoprotein (MOG) inflammatory demyelinating disease with human herpesviruses 7 (HHV-7) infection. Methods: The detailed clinical characteristics, neuroimaging features, and outcomes of the patient were collected. Polymerase chain reaction (PCR), cell-based assay (CBA) and the tissue-based indirect immunofluorescence assay (TBA) were used for diagnosis. Results: The clinical manifestations included headache, dizziness, fever, optic neuritis, and epileptic-seizures. Brain magnetic resonance imaging (MRI) showed hyperintensities involving the left frontal, orbital gyrus and bilateral optic nerve with substantial contrast enhancement. Moreover, test for HHV-7 DNA by using the next generation sequencing metagenomics and polymerase chain reaction showed positive result in CSF but not in the serum samples. Anti-HHV-7 IgM and IgG antibodies were detected in both the serum and cerebrospinal fluid. NMDAR antibodies (1:10) were found positive in the patient’s CSF by a cell-based assay, and MOG antibodies were positive in the serum (1:10) and CSF (1:32). The patient appeared to respond well to immune therapy and it was found that the clinical symptoms including epileptic-seizure as well as headache were relieved and cerebral lesions almost disappeared after the treatment. However, his vision was not completely restored even at the 8-month follow-up, especially the vision in his right eye which was more seriously damaged. Discussion: We report a rare case of MOG antibodies and anti-NMDAR encephalitis overlapping syndrome (MNOS) with HHV-7 infection for the first time. The possibility of MNOS needs be considered when optic neuritis occurs in the patients diagnosed with anti-NMDAR encephalitis. Besides, immunotherapy should be initiated as early as possible to improve the treatment outcomes and facilitate complete cure.